Research advances in traditional Chinese medicine formulae and active components targeting lipid metabolism for hepatocellular carcinoma therapy - Liu, Yang; Yang, Jie; Yu, Fenghua; Li, Li; Zhao, Ning; Lu, Cheng; Lu, Aiping; He, Xiaojuan (Frontiers in Pharmacology, 2025)
Hepatocellular carcinoma (HCC) has a relatively poor prognosis and a high degree of malignancy. However, the therapeutic drugs are limited. In recent years, abnormal lipid metabolism and its important role in HCC has been reported, and emerging studies found that some formulae and active components of traditional Chinese medicine (TCM) can regulate abnormal lipid metabolism in HCC, showing their good application prospects. Therefore, this article summarizes the changes and the roles of lipid metabolites in HCC progression, and discusses the role of formulae and active components of TCM for the treatment of HCC based on their regulation on abnormal lipid metabolism. A deeper understanding of their relationship may help the precise use of these formulae and active components in HCC.